2015
DOI: 10.23937/2572-4142.1510002
|View full text |Cite
|
Sign up to set email alerts
|

A New Animal Model to Study Endogenous Cardiotonic Steroids and the Progression of Cardiovascular Events in Salt-Sensitive Hypertension

Abstract: The Dahl salt-sensitive rat is a well-established model to study essential hypertension. We first described a subgroup of these rats based on the unique response pattern in systolic blood pressure during the first weeks of exposure to a high salt diet that included cataract formation. We classified this group as cataract-prone Dahl salt-sensitive rat. We also were able to predict and prevent cataract formation in these rats. Further studies showed an inhibition of lens Na, KATPase activity which may be in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Salt-sensitive blood pressure has been shown to be a risk factor for cardiovascular morbidity and mortality with a similar or higher impact on health than increased BP alone [46]. Using the Dahl salt-sensitive (DS) rat as a model of essential hypertension, we previously reported that total CTS (digoxin-like immunoreactive factor, DLIF) was the same independent of the blood pressure response to high salt and only the free, unbound circulating DLIF increased in those DS rats that had a higher sensitivity to salt intake [7]. This variability in blood pressure response to high salt diet and unevenness in circulating of unbound MBG levels is also found in salt-sensitive subjects with sex-specific [23] and race-related associations [24].…”
Section: Discussionmentioning
confidence: 99%
“…Salt-sensitive blood pressure has been shown to be a risk factor for cardiovascular morbidity and mortality with a similar or higher impact on health than increased BP alone [46]. Using the Dahl salt-sensitive (DS) rat as a model of essential hypertension, we previously reported that total CTS (digoxin-like immunoreactive factor, DLIF) was the same independent of the blood pressure response to high salt and only the free, unbound circulating DLIF increased in those DS rats that had a higher sensitivity to salt intake [7]. This variability in blood pressure response to high salt diet and unevenness in circulating of unbound MBG levels is also found in salt-sensitive subjects with sex-specific [23] and race-related associations [24].…”
Section: Discussionmentioning
confidence: 99%
“…Salt-sensitive blood pressure has been shown to be a risk factor for cardiovascular morbidity and mortality with a similar or higher impact on health than increased BP alone [4][5][6]. Using the Dahl salt-sensitive (DS) rat as a model of essential hypertension, we previously reported that total CTS (digoxin-like immunoreactive factor, DLIF) was the same independent of the blood pressure response to high salt and only the free, unbound circulating DLIF increased in those DS rats that had a higher sensitivity to salt intake [7]. This variability in blood pressure response to high salt diet and unevenness in circulating of unbound MBG levels is also found in salt-sensitive subjects with sex-specific [23] and race-related associations [24].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in salt intake increases the circulating level of cardiotonic steroids (CTS) in both experimental animal and human subjects [7,8]. Endogenous cardiotonic steroids are a group of hormones that have in common a steroid structure and their ability to inhibit or modulate the activity of the Na, K ATPase [9].…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies from our laboratory published in the late 1990s and early 2000s revealed that CTS could stimulate protein tyrosine phosphorylation and a number of growth-related pathways in cell type- and tissue type-dependent manner [ 53 , 54 , 55 , 56 , 57 ], which has now been largely confirmed by studies from other laboratories around the world [ 49 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. These new findings suggest NKA as an important signal transducer, and the involvement of protein kinase cascades in the cell growth regulation by CTS rather than the inhibition of ATPase activity.…”
Section: Na/k-atpase and Signal Transductionmentioning
confidence: 91%